Evaluasi Kinerja Penyelenggara Pemilu pada Pilkada 2024 di Kabupaten Pasaman - Najwa Prita Yunas; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
The Regional Head Election (Pilkada) is one of the democratic instruments for realizing democratic and integrity-based regional governance. However, the implementation of repeat voting (PSU) in the 2024 Pilkada in Pasaman Regency indicates the need to evaluate the performance of election administrators. This study aims to analyze the performance of election administrators in the 2024 Pilkada in Pasaman Regency and to identify the supporting and inhibiting factors in its implementation. The study employed a qualitative approach using a descriptive method. Informants were selected through purposive sampling. Data were collected through observation, interviews, and documentation and were then analyzed using Miles and Huberman’s interactive analysis model, which comprises data reduction, data presentation, and conclusion drawing. The results show that the performance of the General Election Commission, Election Supervisory Agency, and Polling Station Working Committee in the 2024 Pilkada in Pasaman Regency was generally satisfactory based on the indicators of productivity, service quality, responsiveness, responsibility, and accountability. This performance was supported by stakeholder involvement and the availability of regulations and technical guidelines but still faced obstacles in the form of local political dynamics, time constraints, and the complexity of the Pilkada stages. The findings also indicate the need for improvements in administrative verification, public communication, and interinstitutional coordination. This study confirms that strengthening institutional capacity and coordination among election administrators is necessary to improve the professionalism, integrity, and quality of future Pilkada implementation.